Management accounting systems in Finnish service firms - Hussain, Md. Mostaque; Gunasekaran, A.; Laitinen, Erkki K.
Based on a study of thirty-two Finnish service firms in late 1993, the authors found that Management Accounting System such as Activity Based Costing (ABC) were not frequently used, even though they would be helpful in appreciating real production costs.
This study deals with management accounting practices in small and medium sized service firms in Finland. The recent trends of Management Accounting Systems (MAS), such as Activity Based Costing (ABC), are not frequently used in Finnish service organizations, although these practices have been realized by the majority of respondents to be an important tool to understand real product costs, decrease production costs, modernize cost accounting systems and identify activity costs. An empirical study indicates that a few Finnish small and medium sized service organizations have implemented recent developments of MAS such as ABC. The practices of MAS do not vary with differences in type of service firms that were included in this study. This paper demonstrates that MAS are not very successful in the Finnish service organizations investigated to achieve the goal of decision making, planning and management control, and to improve the information system within the organizations.
Keywords: Management accounting systems; Finnish service firms